Pendidikan Kesehatan Menggunakan Video Edukatif terhadap Pencegahan Kegawatdaruratan Kehamilan Akibat Infeksi Saluran Kemih - Mar'atun Ulaa; Windy Astuti Cahya Ningrum; Mareta Kurniati (Jurnal Keperawatan Silampari, 2022)
This study aims to determine the effectiveness of health education in preventing emergency pregnancy due to urinary tract infections at Muhammadiyah Hospital Palembang. This research method is a quantitative research using Quasi Experiment research with a non-equivalent pretest-posttest non-control group design. The results showed that of 29 respondents, 57% were aged 18-25 years, 55% had nulliparous parity status, 66% had last education SMA/SMK, and 38% were homemakers. Statistical test results found that p-value 0.000 <0.05. In conclusion, health education on the prevention of emergency pregnancy is effective in increasing respondents' knowledge. Keywords: UTI, Emergency Pregnancy, Health Education